Sustainability in university campuses : the way forward - Walter Leal Filho (Springer, 2019)
This short, final chapter, summarises the state of the art and outlines some of the areas where improvements in respect of the promotion of sustainability on campuses are needed.
Keywords: Campuses; Innovation; Resources; Sustainability; Synergies